2016
DOI: 10.1007/s12041-015-0600-3
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila bipectinata species complex: degree of sterility and dystrophied ovaries in interspecific hybrid females

Abstract: Banerjee P. and Singh B. N. 2016 The Drosophila bipectinata species complex: degree of sterility and dystrophied ovaries in interspecific hybrid females. J. Genet. 95, [167][168][169][170]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, we planned to investigate this further and check the fertility of hybrid daughters from all the crosses. We found that daughters having D. pseudoananassae as one of their parents had drastically reduced fertility compared to the parental females (Banerjee and Singh 2015b). In the crosses D. pseudoananassae females 9 D. bipectinata males and D. pseudoananassae females 9 D. parabipectinata males, the hybrid sons were found to have severely compromised eye symmetry and poor viability.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, we planned to investigate this further and check the fertility of hybrid daughters from all the crosses. We found that daughters having D. pseudoananassae as one of their parents had drastically reduced fertility compared to the parental females (Banerjee and Singh 2015b). In the crosses D. pseudoananassae females 9 D. bipectinata males and D. pseudoananassae females 9 D. parabipectinata males, the hybrid sons were found to have severely compromised eye symmetry and poor viability.…”
Section: Discussionmentioning
confidence: 77%
“…For the fertility assay, we checked the larval activity. This procedure was earlier used by Kim and Watanabe (1989) and Banerjee and Singh (2016). All the experiments of fertility assay were categorised into two groups that was group I and group II.…”
Section: Fertility Assaymentioning
confidence: 99%